Kelebihan dan kekurangan penggunaan radiasi dosis rendah (Low Doses Radiation: advantages and disadvantages) - Lusi Epsilawati; Azhari Azhari; Bremmy Laksono; Haris Nasutianto; Eha Renwi Astuti (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: To inform and discuss the benefits and harms of low dose radiation. Literature Review: Low dose radiation (LDR) was often used, including for services in the field of dentistry. Several studies have studied this for a long time but the results are still not conclusively agreed. Some researchers found a variety of side effects that are not beneficial to the body, but some found no association with the body damage caused by this, and even some found that LDR has beneficial effects on the body. Conclusion: low doses of radiation cause significant changes in the body, although this condition is met with an adaptive reaction which is considered a beneficial response by the body. Therefore, no matter how small the radiation is given, it will still have an impact on the body so it is better to be wise in its use.